2021
DOI: 10.3390/ma14102641
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Properties of Cement with Liquefied Red Mud Neutralized by Nitric Acid

Abstract: An increasing amount of red mud (RM) is being generated globally due to the growth in aluminum production. To avoid RM pollution, low-cost methods for effectively recycling RM are being investigated. We propose a method for recycling RM as a construction material. Liquefied RM (LRM) was neutralized by nitric acid and added to cement paste, and the hydration heat, compressive strength, and hydration products were investigated. The cement paste with neutralized LRM had a higher compressive strength than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Meanwhile, the values of UCS for the D-3 sample (30% CP) and group E samples (40% CP) show a slight increase. Previous investigations have shown that the strength of the CGFB samples is mainly determined by the cement hydration [30][31][32][33][34]. Generally, the stronger the cement hydration is, the larger the corresponding strength of the CGFB sample is.…”
Section: Uniaxial Compression Test Resultsmentioning
confidence: 99%
“…Meanwhile, the values of UCS for the D-3 sample (30% CP) and group E samples (40% CP) show a slight increase. Previous investigations have shown that the strength of the CGFB samples is mainly determined by the cement hydration [30][31][32][33][34]. Generally, the stronger the cement hydration is, the larger the corresponding strength of the CGFB sample is.…”
Section: Uniaxial Compression Test Resultsmentioning
confidence: 99%
“…However, this recycling process is complex and economically inefficient. The red mud’s recycling rate has typically stayed within 10% [ 17 ]. In previous studies, liquefied red mud (LRM) was neutralized with sulfuric acid (LRM + S) or nitric acid and was added to cement paste to improve the economic efficiency and recycling rate [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%